1999
DOI: 10.1074/jbc.274.13.8445
|View full text |Cite
|
Sign up to set email alerts
|

Identification of d-Proline Reductase fromClostridium sticklandiias a Selenoenzyme and Indications for a Catalytically Active Pyruvoyl Group Derived from a Cysteine Residue by Cleavage of a Proprotein

Abstract: Highly active D-proline reductase was obtained from Clostridium sticklandii by a modified purification scheme. The cytoplasmic enzyme had a molecular mass of about 870 kDa and was composed of three subunits with molecular masses of 23, 26, and 45 kDa. The 23-kDa subunit contained a carbonyl group at its N terminus, which could either be labeled with fluorescein thiosemicarbazide or removed by o-phenylenediamine; thus, Nterminal sequencing became feasible for this subunit. L-[14 C]proline was covalently bound t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 42 publications
0
82
1
Order By: Relevance
“…3B). The organization of this operon is also identical to that found in C. sticklandii, with the exception of a duplication of prdE in C. difficile (21). Located downstream, and potentially within the same operon of the prd genes, is an open reading frame predicted to encode the proline racemase (prdF).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…3B). The organization of this operon is also identical to that found in C. sticklandii, with the exception of a duplication of prdE in C. difficile (21). Located downstream, and potentially within the same operon of the prd genes, is an open reading frame predicted to encode the proline racemase (prdF).…”
Section: Resultsmentioning
confidence: 81%
“…Studies by Andreesen and his colleagues have also demonstrated that glycine derivatives (betaine and sarcosine) can also act as Stickland acceptors in E. acidaminophilum (1,33), and the enzymes catalyzing the reduction of these amino acids are likely to contain the core subunits from the glycine reductase (1). Kabisch et al also uncovered a selenoprotein subunit in the D-proline reductase (21). It should be noted that in the initial description of C. sticklandii, Stadtman and McClung reported that the closest related strain (based on biochemical characteristics) was the poorly understood C. difficile (45).…”
mentioning
confidence: 99%
“…Most prokaryotic selenoproteins, however, are unique and catalyze highly-varied processes that have not been discovered in eukarya. In the clostridial cluster XI (Kreimer and Andreesen, 1995;Wagner et al, 1999;Kabisch et al, 1999), selenoproteins are vital for energy production, particularly under stress, and appear to be important for additional metabolic performances and pathogenicity. A better understanding of such unique pathways in clinically relevant microorganisms might provide a rational basis for therapeutic intervention.…”
Section: Identified Selenoproteinsmentioning
confidence: 99%
“…12 , 13 Notably, ∼65% of the Clostridiales species that possess the prd operon, which is essential for Pro reduction, also encode HypD. 13 , 14 In these species, the conserved proC gene (encoding P5CR) adjacent to hypD provides a strong indication that Hyp is metabolized to Pro and used as an electron acceptor. In Stickland fermentation, Pro is metabolized via a 2-step pathway to 5-aminovalerate, which often accumulates as an end product (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2A). 14 , 15 To test whether HypD-encoding Clostridiales consume Hyp via this pathway, we examined two strains encoding both hypD and the prd operon ( C. difficile  630Δerm and Terrisporobacter glycolicus DSM 1288). We confirmed that they generate 5-aminovalerate when grown in the presence of Hyp (Fig.…”
Section: Introductionmentioning
confidence: 99%